2020
DOI: 10.3390/ani10050820
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 1 (AQP1) Expression in Healthy Dog Tears

Abstract: Aquaporins (AQPs) are a family of thirteen membrane proteins that play an essential role in the transport of fluids across the cell plasma membrane. Recently, the expression of AQPs in different ocular tissues and their involvement in the pathophysiology of eye diseases, have garnered attention. Considering that literature on AQP expression in the lacrimal glands and their secretion is scarce, we aimed to characterise AQP1 expression in the tears of healthy dogs using two tear collection methods (Schirmer tear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In veterinary medicine, recent interesting investigations regarding canine tears have been reported, such as the presence of AQPs (AQP0, AQP1, AQP3–5 and AQP9) in different canine ocular tissues [ 6 ]. The expression of aquaporin-1 (AQP1) by Western blot analysis was found in canine eye tears, suggesting its specific role in tear secretion [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine, recent interesting investigations regarding canine tears have been reported, such as the presence of AQPs (AQP0, AQP1, AQP3–5 and AQP9) in different canine ocular tissues [ 6 ]. The expression of aquaporin-1 (AQP1) by Western blot analysis was found in canine eye tears, suggesting its specific role in tear secretion [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Schirmer strips have been used for comprehensive proteomic studies in dogs 9,39 and identification of individual proteins such as aquaporins in tears. 40…”
Section: Discussionmentioning
confidence: 99%
“…The collected data indicate the role of AQPs in water management in a dog's eye. AQP1 has also been shown to play an important role in producing tears in healthy dogs (37). It is likewise suggested that deficiency of AQP5 in the lacrimal glands and nictitating membrane glands in dogs may be correlated with keratoconjunctivitis sicca (71).…”
Section: Aquaporins In Caninesmentioning
confidence: 99%